Korban Cyberbullying, Siapakah? - Barus, Rehia Karenina Isabella (Universitas Medan Area, 2019)
Cyberbullying is a new form of bullying that is commonly experienced in the real world but with the same characteristics and effects. Cyberbullying is the behavior of using information and communication technology that aims to intimidate others repeatedly and intentionally Victims of cyberbullying are